An Approach to the Study of Income, Utility, and Horizontal Equity - Rosen, Harvey S. (Quarterly Journal of Economics, 1978)
I. Introduction, 307.—II. Utility functions and differences in tastes, 308.—III. Measuring horizontal equity, 313.—IV. Qualifications, 318.